Human-generative AI collaboration enhances task performance but undermines human’s intrinsic motivation - Suqing Wu; Yukun Liu; Mengqi Ruan; Siyu Chen; Xiao-Yun Xie (Scientific Reports)
Abstract In a series of four online experimental studies (total N = 3,562), we investigated the performance augmentation effect and psychological deprivation effect of human-generative AI (GenAI) collaboration in professional settings. Our findings consistently demonstrated that collaboration with GenAI enhanced immediate task performance. However, this performance augmentation effect did not persist in subsequent tasks performed independently by humans. Importantly, transitioning from collaboration with GenAI to solo work led to an increased sense of control of human workers, and was also accompanied by significant decreases in intrinsic motivation and increases in feelings of boredom. These results highlight the complex dual effects of human-GenAI collaboration: It enhances immediate task performance but can undermine long-term psychological experiences of human workers.